Analysis of Factors Affecting the Growth and Development of Maize Crops (Zea Mays L) in Adiankoting Sipoholon and Paranginan Districts - Panjaitan, Nixson; Simangunsong, Saudur; Simatupang, Lambok; Purba, Weslyh (International Journal of Environment, Agriculture and Biotechnology, 2023)
This study aims to determine the factors that affect the growth and development of corn plants (zea mays l.) in the sub-districts of Adiankoting, Sipoholon and Paranginan. This study uses the Statistical Package Social Sciences (SPSS) stastika formula consisting of each sub-district using 50 questionnaires from Adiankoting sub-district 50 questionnaires, from Sipoholon sub-district 50 questionnaires and from Paranginan sub-district 50 questionnaires, and the total amount to 150 questionnaires. This research was conducted by a direct field survey system and interviews with respondents or corn farmers in each of the 150 farmers, the results of this study indicate that in each sub-district there are different and some are the same in terms of altitude, land area, planting distance, age of farmers and others. The three sub-districts are dominated by male farmers, mostly only diparanginan more female farmers but maybe in other areas or in other villages there may also be many female farmers. I conducted this research during October to November 2021 where there is still strict health protocol supervision because corona has spread everywhere, so caution is needed. In the Adiankoting, Sipoholon and Paranginan sub-districts, the various types of fertilizers used and the way they are applied and pests and diseases are too many to attack in these areas.